Validitas LKS berorientasi HOTS dalam model inkuiri terbimbing pada materi momentum impuls dan getaran harmonis di kelas X SMA/MA - Nurhasanah Nurhasanah; Silvi yulia sari; Yenni Darvina; Yohandri Yohandri (PILLAR OF PHYSICS EDUCATION, 2019)
The purpose of this study was to determine the validity of the HOTS-oriented worksheets in the guided inquiry model on the material of impulse momentum and harmonic vibrations in class X SMA/MA. The study was Research and Development (R&D) by using Borg and Gall model, which consisted of potensial problems, data collection, product design, design validations, product trials, product revisions, trial usage, product revisions and mass products. However, this research was limited to the design revision. Validation is done using instruments which was filled by experts. The validation of this research was carried out by three physics lecturers at the Faculty of Mathematics and Natural Sciences Padang State University. Based on the validation result by three validators, the validity obtained were 93.1 % in a very valid category. This means that HOTS-oriented worksheets in the guided inquiry model can be used in the physics learning process on impulse momentum and harmonic vibrations in class X SMA/MA.